A participatory project for the Librino Social Housing Community. - Stefania De Medici; Giulia Marchiano; Maria Rita Pinto (Vitruvio: International Journal of Architectural Technology and Sustainability, 2023)
Social housing is the outcome of policymaking aimed at guaranteeing adequate living conditions for disadvantaged social groups. In Italy, in the post-war reconstruction period, buildings designed by internationally renowned architects, led to results of such high design quality that it is essential to preserve them. Nevertheless, their advanced degradation and functional obsolescence are due to being built with construction systems focused on quick completion and cost-effectiveness, as well as a lack of maintenance. Such conditions now impose performance upgrades and reuse for services and collective spaces. The paper addresses the issue of the recovery of this housing stock in the Italian context, analyzing the case of Librino (Catania). The research question is based on evidence that the lack of services and collective spaces in the suburbs leads people to move to other areas of the city for work, health, education, culture, and leisure. The proposed approach investigates the overall organization of the neighborhood, up to reuse pilots, as for the Moncada Theater, to improve the overall quality and attractiveness of the area, even with minor renovations. The theatre, which was abandoned before completion, is an example of how only housing was built or completed in residential areas designed to provide a wide range of services for citizens as a result of a funding shortfall. Reuse decisions are the result of user involvement with a view to social and cultural sustainability.